Tariff Impact on the Domestic Price of Vegetable Oil in Iran and the Associated Issues - omid gilanpour; A. Valimohammdi (مجله اقتصاد و توسعه کشاورزی, 2015)
This study uses vector error correction model to examine the effects of oilseeds, crude oil and vegetable oil tariffs on vegetable oil consumer price. Monthly data sets for the years 2004-2013 and VAR and VECM models were applied for this study. Research findings indicates only a long term equilibrium relation between the study variables .The effect of vegetable oil tariffs on consumer and producer price index are 0.4 and 0.07, respectively. Furthermore, one percent increase in the oil seeds and crude oil tariff, will increase consumer prices by 2.35, 0.19percent. The huge gap between the impacts of the two tariffs –e.g. oilseeds and crude oil tariffs- on consumer price shows that oil industries work with low efficiency. This practically doubles the impact of tariff on consumers. Accordingly, structural reform in the oil industry can develop oil production and prevent additional burden upon the consumer price.